NOMINEE AGREEMENT: A SOLUTION FOR FOREIGNERS TO CONTROL LAND IN BALI - Tjokorda Gde Rai Y. Ary Sudharsana; I Wayan Novy Purwanto (Transpublika Publisher, 2022)
The purpose of this study is to find out the legal basis of the nominee agreement and to find out the nominee agreement that is used as a solution by foreigners in controlling land in Bali. This research method uses the type of empirical legal research. The legal basis for the nominee agreement is Article 21 and Article 26 of the Basic Agrarian Law (BAL). In addition, there are also other legal bases, namely Articles 1320 and 1313 of the Civil Code. Juridically, the nominee agreement cannot be used as a solution by foreigners to control land in Bali. Land tenure that can be taken by foreigners is with usufructuary rights and rental rights.